1993
DOI: 10.1159/000187371
|View full text |Cite
|
Sign up to set email alerts
|

Wegener’s Granulomatosis with Antiproteinase-3 Antibodies Occurring after Hodgkin’s Disease

Abstract: We describe the first association between Hodgkin’s lymphoma and Wegener’s granulomatosis, heralded by renal involvement. A 43-year-old man developed rapidly progressive glomerulonephritis requiring chronic hemodialysis 8 months after remission of Hodgkin’s lymphoma. At that moment, no extrarenal involvement was found, despite extensive investigation. Antineutrophil cytoplasm antibodies were positive, without specificity for proteinase-3 or myeloperoxydase. Six months after beginning hemodialysis, multiple pul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

1994
1994
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…A 4–11‐fold increased risk for developing lymphomas has been observed in patients with Wegener's granulomatosis (6, 7), while an increased risk for lymphoma has also been reported in other rheumatic conditions (8, 9). An interesting case of Wegener's granulomatosis developing in a patient in remission for Hodgkin's lymphoma has also been described (10). Altered immune tolerance associated with these lymphoproliferative diseases or with the immunosuppressive therapy used to treat these diseases probably also plays a role.…”
Section: Discussionmentioning
confidence: 99%
“…A 4–11‐fold increased risk for developing lymphomas has been observed in patients with Wegener's granulomatosis (6, 7), while an increased risk for lymphoma has also been reported in other rheumatic conditions (8, 9). An interesting case of Wegener's granulomatosis developing in a patient in remission for Hodgkin's lymphoma has also been described (10). Altered immune tolerance associated with these lymphoproliferative diseases or with the immunosuppressive therapy used to treat these diseases probably also plays a role.…”
Section: Discussionmentioning
confidence: 99%
“…[10][11][12][13][14] In the present case, the patient had sinusitis and the titer of PR3-ANCA was high, but the histology demonstrated small vessel vasculitis without granu- There are only five such cases with a definitive diagnosis of vasculitis confirmed by biopsy reported in the literature (Table 1). 6,[16][17][18] Two cases were positive for MPO-ANCA or p-ANCA, and three cases were positive for PR3-ANCA or c-ANCA. Four cases were B-cell malignancies and one case was a T-cell malignancy.…”
Section: Discussionmentioning
confidence: 99%
“…6 In the remaining case, AAV was followed by lymphoma, suggesting that an immunosuppressive state or the use of cytotoxic drugs, such as cyclophosphamide, might cause lymphoproliferative disorders. 16,18 In the pathogenesis of AAV, ANCA activates neutrophils and vascular endothelial cells. 19 Activated endothelial cells up-regulate adhesion molecules and we could speculate that lymphoma cells can easily aggregate in the microvasculature.…”
Section: Discussionmentioning
confidence: 99%
“…More recently, a patient with crescentic glo merulonephritis due to Wegener's granulomatosis with c-ANCA. after remission of Hodgkin's lymphoma, has been reported [19], However, the association of monoclonal gammopathy with crescentic glomerulonephritis is very unusual [2][3][4], Experimental studies [20] have demonstrated that a proliferative glomerulonephritis may be induced by plasmocytomas secreting monoclonal immunoglobulins. In addition, the observation that a reduction of the mono- Martin/Martinez Ara/Picazo/PascualSalcedo/Garda Puig/Torre-Carballada/Gil clonal component with plasma exchange was associated with an improvement of glomerular lesions and renal function, strongly favors the hypothesis that plasma cell dyscrasia may trigger a glomerulopathy [3,21].…”
Section: Discussionmentioning
confidence: 99%